2018
DOI: 10.4041/kjod.2018.48.4.245
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different primers on indirect orthodontic bonding: Shear bond strength, color change, and enamel roughness

Abstract: ObjectiveWe aimed to perform in-vitro evaluation to compare 1) shear bond strength (SBS), adhesive remnant index (ARI), and color change between self-etched and acid-etched primers; 2) the SBS, ARI and color change between direct and indirect bonding; and 3) the enamel roughness (ER) between 12-blade bur and aluminum oxide polisher debonding methods.MethodsSeventy bovine incisors were distributed in seven groups: control (no bonding), direct (DTBX), and 5 indirect bonding (ITBX, IZ350, ISONDHI, ISEP, and ITBXp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Concerning the bond strength studies performed using Transbond XT, as was preferred in the present study, the mean bond strength value was found to be 23.47 MPa by D'Attilio, Traini, Di Iorio, et al (2005) 13.60 MPa by Queirioz Tavares, Elias, and Nojima (2018) and 9.86 MPa by İşman, Karaarslan, Okşayan, et al (2012). Regarding all these studies, it was observed that different bond strength values were obtained even though the same adhesive was used.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Concerning the bond strength studies performed using Transbond XT, as was preferred in the present study, the mean bond strength value was found to be 23.47 MPa by D'Attilio, Traini, Di Iorio, et al (2005) 13.60 MPa by Queirioz Tavares, Elias, and Nojima (2018) and 9.86 MPa by İşman, Karaarslan, Okşayan, et al (2012). Regarding all these studies, it was observed that different bond strength values were obtained even though the same adhesive was used.…”
Section: Discussionmentioning
confidence: 46%
“…Regarding all these studies, it was observed that different bond strength values were obtained even though the same adhesive was used. Based on the reference range of bond strength defined by Reynolds and Von Fraunhofer (1977) for clinical success, the bond strength values obtained in the above mentioned studies were considered acceptable D'Attilio et al (2005), Queirioz Tavares et al (2018) and İşman et al (2012). It was stated that such different bond strength values in the literature might have arisen from the parameters in the bond strength test, type of tooth, and the differences between the teeth groups (Mansour & Bakhsh, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated based on a power analysis using G*Power Software version 3.1.9.2 (Universität Düsseldorf, Germany) for shear bond strength at alpha error probability of 0.05 and a power of 95%. 18 The power analysis showed that a total of 10 samples (effect size = 3.375645) was enough, while reliable results could be determined using 80 premolar teeth. Subsequently, 80 freshly extracted premolars for orthodontic reasons were used in this in vitro study.…”
Section: Methodsmentioning
confidence: 97%
“…This way, the tooth surface is customized, and shear bond strength is increased. Queiróz Tavares et al 2 found that flowable resins are an excellent bonding material for these cases, and its bond strength is equal to or greater than that obtained with conventional direct bonding. Chemically cured resins type A or B used for indirect bonding are no longer indicated for this purpose because of their low shear bond strength 2 …”
mentioning
confidence: 98%
“…Both indirect bonding techniques have shear bond strength that is equal to or greater than that of direct bonding 2 3 Digital indirect bonding uses prototyped guides, a technique in which the brackets are positioned directly according to the tie-wings and transferred to the oral cavity.…”
mentioning
confidence: 99%